Novel anti-Sialyl-Tn monoclonal antibodies and antibody-drug conjugates demonstrate tumor specificity and anti-tumor activity. Issue 4 (19th May 2017) - Prendergast, Jillian M.; Galvao da Silva, Ana Paula; Eavarone, David A.; Ghaderi, Darius; Zhang, Mai; Brady, Dane; Wicks, Joan; DeSander, Julie; Behrens, Jeff; Rueda, Bo R.
ABSTRACT: Targeted therapeutics that can differentiate between normal and malignant tumor cells represent the ideal standard for the development of a successful anti-cancer strategy. The Sialyl-Thomsen-nouveau antigen (STn or Sialyl-Tn, also known as CD175s) is rarely seen in normal adult tissues, but it is abundantly expressed in many types of human epithelial cancers. We have identified novel antibodies that specifically target with high affinity the STn glycan independent of its carrier protein, affording the potential to recognize a wider array of cancer-specific sialylated proteins. A panel of murine monoclonal anti-STn therapeutic antibodies were generated and their binding specificity and efficacy were characterized in vitro and in in vivo murine cancer models. A subset of these antibodies were conjugated to monomethyl auristatin E (MMAE) to generate antibody-drug conjugates (ADCs). These ADCs demonstrated in vitro efficacy in STn-expressing cell lines and significant tumor growth inhibition in STn-expressing tumor xenograft cancer models with no evidence of overt toxicity.